2015
DOI: 10.17219/acem/38169
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electromagnetic Radiation of Different Parameters on Platelet Oxygen Metabolism – In Vitro Studies

Abstract: Background. Electromagnetic radiation emitted by a variety of devices, e.g. cell phones, computers and microwaves, interacts with the human body in many ways. Research studies carried out in the last few decades have not yet resolved the issue of the effect of this factor on the human body and many questions are left without an unequivocal answer. Various biological and health-related effects have not been fully recognized. Thus further studies in this area are justified. Objectives. A comparison of changes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…Another study has demonstrated that the low frequency electromagnetic fields generated by car electronics, physiotherapy equipment and LCD monitors may be the cause of oxidative stress in the human body. During this experiment an increase in catalase activity and MDA concentration is observed after 30 min exposure of platelets to EMF regardless of the radiation source [21]. The obtained results are similar to the ones as the outcome of this study excluding the observation time (our study has indicated increase in MDA concentration after 60 min exposure and insignificant increase after 30 min exposure).…”
Section: Discussionsupporting
confidence: 88%
“…Another study has demonstrated that the low frequency electromagnetic fields generated by car electronics, physiotherapy equipment and LCD monitors may be the cause of oxidative stress in the human body. During this experiment an increase in catalase activity and MDA concentration is observed after 30 min exposure of platelets to EMF regardless of the radiation source [21]. The obtained results are similar to the ones as the outcome of this study excluding the observation time (our study has indicated increase in MDA concentration after 60 min exposure and insignificant increase after 30 min exposure).…”
Section: Discussionsupporting
confidence: 88%
“…Ehnert et al [80] found ELF-MF-induced (16 Hz 6-282 µT) increase of SOD2, CAT, GPX3, and glutathione-disulfide reductase (GSR) activity concomitant with the reduction of ROS levels in human osteoblasts. Similarly, in the myelogenous leukemia cell line K562 exposed to ELF-MF (50 Hz, 1 mT) and in human blood platelets exposed to different sources of electromagnetic radiation (1 kHz, 0.5 mT; 50 Hz, 10 mT; or 1 kHz 220 V/m) CAT activity was increased [81,82]. Moreover, the exposure IMR-90 human lung fibroblasts for a total of 168 h to 6 mT ELF-MF contributed to decreased ROS level [83].…”
Section: Oxidative Stress and Antioxidant Statusmentioning
confidence: 91%
“…Oxidative stress can be caused by various environmental factors, including chemical and physical pollution, behavior factors, such as cigarette smoke and alcohol, as well as certain nutrients, such as saturated fat. In addition, a number of reports have examined the effects of electromagnetic radiation (EMR) exposure on the oxidative metabolism of cells [1,2]; these range from increased lipid peroxidation caused by ROS to changes in the activity of antioxidant enzymes in various cells and tissues [3].…”
Section: Introductionmentioning
confidence: 99%